PENERAPAN SISTEM AKUNTANSI PERSEDIAAN BARANG DAGANG PADA SUNRISE DISTRO DENGAN APLIKASI ACCURATE ACCOUNTING - Atmoko, Agus Dwi; Septiana, Ervani Nur (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
Accounting systems include all forms of management information systems that help collect, record, store, and also provide financial accounting information within a company in the process of accounting transactions. Distro Sunrise is one of the Small and Medium Micro Enterprises (MSMEs) located at Jl. Sawunggalih No. 142B Semawung Daleman Village Kutoarjo District engaged in trade by selling apparel. Based on the analysis that has been done, Sunrise Distro does not have a system of recording inventory, including procedures for recording and spending goods in warehouses that result in the unavailability of valid information about stock cards from merchandise inventory. This research aims to implement a trading inventory accounting system on Kutoarjo Sunrise Distro. The data analysis technique used in this study is a quantitative descriptive data analysis technique. Data collection techniques with interviews, documents and literature studies. Use accurate accounting application version 4. This application is expected to facilitate the recording and processing of stock data for merchandise inventory. Data collection techniques are interviews, documents and literature studies. The results of the study in the form of the proposed implementation of accurate accounting application Version 4 consisting of inventory stock card reports, sales reports, purchase reports and reports as reports